Sosialisasi Penggunaan Analgetik Antipiretik Non Steroid Berhubungan dengan Penderita Gastritis di desa Carawali - Nurlaela Nurlaela; Reny Anggriany Hakim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Antipyretic analgesics are a class of drugs that are most widely used to cure or reduce health problems such as fever, headaches, pain, dizziness, stomach ulcers and others. Meanwhile, gastritis or a term that is often known by the public as ulcer disease or stomach disease is a collection of symptoms that are felt as heartburn. The purpose of this service is to increase public knowledge about the Use of Non-Steroid Antipyretic Analgesics Associated with Gastritis Sufferers in Carawali Village. The method used in this community service is to use a quantitative approach, namely to describe the pattern of use of non-steroidal antipyretic analgesics with high gastritis sufferers in Carawali Village in 2019. The research design used was cross sectional. This cross-sectional design is used to find the relationship between the independent variables and the dependent variable.